2001
DOI: 10.1207/s15327914nc392_18
|View full text |Cite
|
Sign up to set email alerts
|

Acyclic Carotenoids and Their Oxidation Mixtures Inhibit the Growth of HL-60 Human Promyelocytic Leukemia Cells

Abstract: Lycopene has been known as a potential food component for cancer prevention, since tomato consumption was shown to be associated with reduced risk of certain cancers. We used HL-60 cells as a model of cancer cells to investigate whether acyclic carotenoids, such as phytoene, phytofluene, and zeta-carotene present in tomatoes, other than lycopene, as well as oxidation mixtures of these carotenoids, are potentially involved in the cancer-preventive action of tomatoes. When HL-60 cells were grown in the carotenoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
53
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(55 citation statements)
references
References 52 publications
2
53
0
Order By: Relevance
“…The effect of both acyclic carotenes (phytoene, phytofluene, fcarotene and lycopene) and some oxidation products of them in the proliferation of human promyelocytic leukemia cells was studied using in vitro HL-60 cell line cultures [139]. The addition of fcarotene and phytofluene at 10 lM into the culture medium led to inhibition of cell growth relative to the control, the effect being markedly higher in the case of the former (ca.…”
Section: Leukemiamentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of both acyclic carotenes (phytoene, phytofluene, fcarotene and lycopene) and some oxidation products of them in the proliferation of human promyelocytic leukemia cells was studied using in vitro HL-60 cell line cultures [139]. The addition of fcarotene and phytofluene at 10 lM into the culture medium led to inhibition of cell growth relative to the control, the effect being markedly higher in the case of the former (ca.…”
Section: Leukemiamentioning
confidence: 99%
“…68%). It is to be noted that the effect of mixtures of oxidation products of phytoene was not evaluated [139].…”
Section: Leukemiamentioning
confidence: 99%
“…A characteristic structural feature of carotenoid molecules is the conjugated polyene chain, which is prone to undergo autoxidation. Autoxidation products of lycopene have been shown to exert biological effects such as growth inhibition of human leukemia cells (Nara et al 2001), apoptosis induction in human prostate cancer cells (Kotake- Nara et al 2002), and promotion of cell-to-cell communication in rat liver epithelial cells (Aust et al 2003). In the case with growth inhibition, the effect was more pronounced with oxidized lycopene than with the intact compound (Nara et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Further, support to this observation, FUCO treated group showed higher ROS level followed by AST, LUT and control ( Figure 4 and Table 1). Earlier, studies have demonstrated that epoxy xanthophylls such as fucoxanthin and neoxanthin reduce the viability of prostate cancer cells by inducing apoptosis to a greater extent than the lutein, β-carotene and lycopene [46]. In addition, Palozza et al [42] demonstrated that under the experimental condition, carotenoids acts as pro-oxidants predominate over the antioxidant and induce the formation of free radical species, including peroxyl radicals, and responsible for an induction of apoptosis.…”
Section: Discussionmentioning
confidence: 99%